1959
DOI: 10.1302/0301-620x.41b1.137
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Radiological Study of Reiter's Disease, Rheumatoid Arthritis and Ankylosing Spondylitis

Abstract: The radiological appearances in twenty-five patients with Reiter's disease have been compared with those in eighty-one with rheumatoid arthritis and thirty-eight with ankylosing spondylitis. The similarities and differences have been analysed. Changes of periosteal new bone in the calcaneum appear to be the only significant differentiating factor, although minor differences in incidence and distribution occur elsewhere. Sacro-iliitis is a common radiological feature of long-standing Reiter's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

1962
1962
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 13 publications
2
16
1
Order By: Relevance
“…This higher incidence is presumably due to the condition that we specifically enrolled patients with symptomatic heel pain, even though our patients were younger and their disease was of shorter duration than those in previous studies [1,8,9]. In previous studies, AS patients were found to have radiographic changes in their heel bones, such as erosion, spurs and periostitis [1,4,13]. Such lesions, which develop as a result of inflammatory processes on entheses, may not be disease-specific but rather late consequences of enthesitis in advanced AS [13,14].…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…This higher incidence is presumably due to the condition that we specifically enrolled patients with symptomatic heel pain, even though our patients were younger and their disease was of shorter duration than those in previous studies [1,8,9]. In previous studies, AS patients were found to have radiographic changes in their heel bones, such as erosion, spurs and periostitis [1,4,13]. Such lesions, which develop as a result of inflammatory processes on entheses, may not be disease-specific but rather late consequences of enthesitis in advanced AS [13,14].…”
Section: Discussionmentioning
confidence: 89%
“…Few reports have investigated the heel conditions of AS patients by plain radiography, and these mainly focused on asymptomatic heels [4,8,9]. In those studies, it was noted that 17% to 58% of patients with AS had radiographic changes in their heels [1,9] and some radiographic alterations were seen in the absence of local symptoms [8,11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations